THE ROLE OF DIGITAL TECHNOLOGY IN PRESERVING LOCAL WISDOM OF CIRENDEU TRADITIONAL VILLAGE: PERSPECTIVE STUDENT PMM 3 UPI - Mutiara saputri; Asmah Amir; Jusman (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to examine how digital technology plays a role in preserving local wisdom in the Cirendeu Traditional Village from the perspective of students of the Independent Student Exchange Program (PMM) 3, Universitas Pendidikan Indonesia (UPI). The research method used is descriptive qualitative with data collection techniques through interviews, observations, and literature studies. The results of the study indicate that digital technology has a significant role in the documentation, education, and promotion of local culture in the Cirendeu Traditional Village through social media, websites, and other digital-based applications. The obstacles faced in the implementation of digital technology are the limited infrastructure and digital literacy of the local community. Therefore, collaboration is needed between students, academics, and the community in developing more effective strategies to utilize digital technology in preserving local culture